Acupuncture for neurogenic bladder due to spinal cord injury: a systematic review protocol. Issue 9 (10th September 2014) - Zhang, Tao; Liu, Huilin; Liu, Zhishun; Wang, Linpeng
Abstract : Introduction: Neurogenic bladder is one of the most common complications following spinal cord injury (SCI). In China, acupuncture therapy is a common treatment for neurogenic bladder due to SCI, but its effects and safety remain uncertain. A protocol is described for a systematic review to investigate the beneficial effects and safety of acupuncture for neurogenic bladder due to SCI. Methods and analysis: Eight databases will be searched from their inception: the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Embase, the China National Knowledge Infrastructure (CNKI), the VIP database, the Wanfang database, the China Doctoral Dissertations Full-text Database (CDFD) and the China Master's Theses Full-text Database (CMFD). Any clinical randomised controlled trials (RCTs) and the first period of randomised cross-over studies related to acupuncture for neurogenic bladder due to SCI will be included. Outcomes will include change in urinary symptoms, urodynamic tests, clinical assessment and quality of life (QoL). The incidence of adverse events will be assessed as the safety outcome. Study selection, data extraction and quality assessment will be performed independently by two reviewers. Assessment of risk of bias, data synthesis and subgroup analysis will be carried out using Review Manager software. Ethics and dissemination: Ethics approval is not required as this is a protocol for a systematic review. The findings of this systematic review will be disseminated via peer-reviewed publications and conference presentations. Trial registration number: PROSPERO (CRD42014010448).